Pretreatment of Huoxue Jiedu Formula Ameliorates Myocardial Ischaemia/Reperfusion Injury by Decreasing Autophagy via Activation of the PI3K/AKT/mTOR Pathway - Long, Linzi; Yu, Zikai; Chen, ShengJun; Wu, Jiarui; Liu, Yingying; Peng, Jun; Qu, Hua; Fu, Changgeng (Frontiers in Pharmacology, 2021)
Background: Myocardial ischaemia/reperfusion (I/R) results in myocardial injury via excessive autophagy. Huoxue Jiedu Formula (HJF) has been widely applied in China for the treatment of ischaemic heart disease. However, the mechanisms of HJF are still poorly understood. Thus, the present experiment was designed to observe the effects of HJF on myocardial I/R injury and explore the possible mechanism. Methods: Myocardial injury in rats subjected to myocardial I/R was reflected by nitrotetrazolium blue chloride staining, thioflavin S staining, serum creatine kinase-MB (CK-MB) and cardiac troponin T (cTnT). Autophagy was determined by electron microscopy, laser confocal microscopy, Q-PCR and western blot. The possible pathway was predicted by network pharmacology and validated in vivo and in vitro. Results: Pretreatment with HJF decreased the no-reflow area, infarcted area, serum CK-MB levels and serum cTnT levels in I/R rat model. In addition, pretreatment with HJF decreased autophagy in heart tissues (decrease in Beclin-1 and LC3-II, and increase in Bcl-2, p62 and ratio of LC3-I/LC3-II). In the vivo study, pretreatment with HJF significantly decreased hypoxia/reoxygenation (H/R)-induced autophagy in H9C2 cells. Network pharmacology was applied to predict the possible mechanism by which HJF affects cardiac autophagy, and the PI3K/AKT/mTOR signalling pathway was the most significantly enriched pathway. And experimental studies demonstrated that pretreatment with HJF increased the phosphorylation of AKT and mTOR, and the effects of HJF on autophagy would be offset by PI3K inhibitor LY294002. Conclusion: Pretreatment with HJF ameliorates myocardial I/R injury by decreasing autophagy through activating PI3K/AKT/mTOR pathway.